Comparative mRNA profile analysis from NAc of adolescent male mice after binge-like alcohol exposure eliciting deficits in context fear extinction learning. - Mario E Lloret Torres; Arelys Rivas Jiménez; Eduardo L Tosado Rodríguez; Kiara Cardona Jordan; Xiany X Lay Rivera; Yaren L Peña Señeriz; Joseph L Capella Muñiz; Marieliz Dieppa Rodríguez; Daniel F Ruiz Bolívar; Jovangelis González Del Toro; John A Florian Alsina; Paola A Colón Rivera; et al. (PLoS ONE)
Introduction Stressor-related disorders frequently co-occur with alcohol use disorder (AUD). This necessitates an understanding of the physiological and genetic factors contributing to this relationship. Binge drinking is the most common method of alcohol consumption among adolescent males and significantly increases the risk of developing comorbid stressor-related disorders and AUD. In experiments modeling the effects of a single binge-like alcohol exposure in male adolescent mice, we observed a clear deficit in context extinction learning. This exposure led to a significant initial increase in subsequent voluntary drinking on day one, as measured by the every-other-day (EOD) two-bottle choice drinking assay, which normalized thereafter. Methods For this study we performed an mRNASeq analysis of mice nucleus accumbens (NAc), a region intricately involved in regulating both aversive contextual fear responses and reward, after EOD to profile the differential expression of mRNAs within this region. We also used immunohistochemistry of coronal brain slices to characterize expression of proteins associated with stress-related disorders and molecular alcohol tolerance, such as FKBP5, GSK3ß, and ß-catenin, within the striatum, nucleus accumbens (NAc), hippocampus, and basolateral amygdala (BLA). Results Comparative mRNA profile analysis reveals significant long-term changes in gene expression induced by binge-like alcohol exposure, even 30 days after the initial exposure. Immunohistochemistry showed a full recovery of previously observed altered levels of target proteins prior to EOD. Conclusions These findings suggest that the temporal activation of specific gene subsets plays a crucial role in the comorbidity of AUD and stressor-related diseases. Understanding these mechanisms can help develop more effective, integrated treatment approaches to improve outcomes for affected individuals.